Predictive and criterion validity of the Cervantes-SF menopause quality of life questionnaire. Issue 8 (August 2021) - Coronado, Pluvio J.; Monroy, Manuel; Fasero, María; Baquedano, Laura; Mendoza, Nicolás; Llaneza, Plácido; Rejas, Javier; Ruiz, Miguel A.
Abstract: Objectives: To determine the predictive and criterion-based validity of the Cervantes-SF scale that measures the impact of menopause on Health-Related Quality of Life. Methods: We recruited a noninstitutionalized sample of peri/postmenopausal women aged 40 to 65 years, who had their last menstrual cycle 12+ months prior to inclusion in the study of the psychometric validity of the Cervantes-SF scale. Predictive validity of the scale was confirmed for various health outcome measures administered concomitantly (years of disability-free life expectancy, work productivity and impact on daily activities, economic impact arising from loss of work productivity, hours of undisturbed sleep each day, and the utilization of healthcare facilities), whilst criterion validity was determined by the likelihood of identifying a moderate-to-severe vasomotor or genital syndrome requiring specific treatment. Results: A sample of 308 peri/postmenopausal women with a mean age of 55.7 years (SD: 5.3 y) was analyzed in this study. A score >25 points on the dimension of vasomotor problems (or menopausal health) showed values of sensitivity and specificity > 80% for identifying women with moderate-severe vasomotor syndrome requiring pharmacological treatment. Predictive validity was confirmed for menopause-related health outcomes. A change of 6.7 points in the scale score, equivalent to the value of its minimal difference, is indicative of a significant increase in the degree of disability regarding work/day-to-day activities, greater economic loss due to decreased work productivity, fewer years of life expectancy without disability, fewer hours of undisturbed sleep, and more visits to the physician per year due to menopausal symptoms. Conclusions: These results confirm the criterion and predictive validity of the Cervantes-SF scale in peri/postmenopausal women. Abstract : Supplemental Digital Content is available in the text